PENGARUH SALES GROWTH, LEVERAGE, CURRENT RATIO DAN ROFITABILITAS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2019)
This study aims to examine how much "Effect of Sales Growth, Levarage, Current Ratio and Profitability on Dividend Payout Ratio in Banking Companies Listed on the Indonesia Stock Exchange". In this study the samples taken were banking companies listed on the Indonesia Stock Exchange in the period 2015-2017. The data analysis method used in this study was using multiple regression analysis. The results of the research partially show that Sales Growth has an effect on Dividend Payout Ratio, Leverage has an effect on Dividend Payout Ratio, Current Ratio has an effect on Dividend Payout Ratio and Profitability has an effect on Dividend Payout Ratio. The results of the study simultaneously show that Sales Growth, Levarage, Current Ratio and Profitability together on Dividend Payout Ratio. It is hoped that this research can be used as a work to add insight into knowledge that can further broaden the mindset of the reader, especially regarding the influence of Sales Growth, Levy, Current Ratio and Profitability on Dividend Payout Ratio in Banking Companies Listed on the Indonesia Stock Exchange.